Pengaruh Pendidikan Kesehatan Dengan Petode Demonstrasi Terhadap Keterampilan Siswa PMR Dalam Tindakan Pertolongan Pertama Pada Syncope Di MAN Model Manado - Cinta Tiara; Faradilla Miftah Suranata; Rahmat Hidayat Djalil (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Fainting or syncope is a condition where a person loses consciousness due to decreased blood flow to the brain. The occurrence of syncope in students at school can occur at any time. Therefore all students should be able to master first aid, at school Students must be able to pelrtollolngan pelrtama when syncope occurs quickly and quickly, even if the meldis assistance is only basic and belrbasis keldolktelran science known to many people.The purpose of this study was to determine the Effect of Health Education with Demonstration Methods on the Skills of PMR Students in First Aid Actions in Syncope at Man Model Manado. This research is a Pre-experiment design with One Group pretest-postest design. The sampling technique is total sampling with 30 respondents. Data collection uses an observation sheet. Analyzed with Mc Stastistic test. Nemar statistical test. From the Results: Mc.Nemar statistical test shows that there is a significant effect between health education with demonstration methods on the skills of PMR students in first aid actions in syncope at Man Model Manado. (p)= 0.000: α = 0.05. Conclusion: in this study there is an effect of Health Education with Demonstration Method on the Skills of PMR Students in First Aid Action on Syncope at Man Model Manado. This research is expected to be a reference for health and education installations in an effort to provide the influence of health education with demonstration methods on student skills in first aid actions in syncope.